NEUROLOGICAL COMPLICATIONS OF HAND, FOOT AND MOUTH DISEASE IN CHILDREN: A REVIEW - Shah, Jahan; Sijun, Liu; Hui, Zhao; Zeb, Falak; Haq, Ijaz UL; Ullah, Amin (Journal of Ayub Medical College Abbottabad, 2020)
Background: Hand-Foot-and-Mouth disease (HFMD) is a viral illness commonly seen in young children, characterized by fever, vomiting, ulcerative lesions in oral mucosa, and vesicles on hands and feet. The early symptoms resolve but sometimes, it leads to more harsh neurological complications and even death. Therefore, the objective of this review was set to provide an overview of the symptoms, pathogenic agents, and treatment of neurological complications associated with HFMD. Methods: We reviewed literature from PubMed and Science Direct covering at least one of our objectives from inception to 4th March 2018. Result: This review represents 6 countries including China, Vietnam, Cambodia, South Korea, Taiwan, and Australia. Fifteen studies with a total of 1043 patients were included. The majority of HFMD cases with neurological complications were reported in China, predominance in boys as compared to girls, with 97% cases under 15 years of age. Meningoencephalitis and brainstem encephalitis contributed 70% of all neurological complications related to HFMD. Human Enterovirus71 genotype C, especially C4a was a causative agent associated with severe complications. Among symptoms, fever, vomiting, myoclonic jerks or seizure, headache, convulsion, and rashes were reported in almost all neurological complications. The common and supportive treatments were the administration of intravenous immunoglobulin and glucocorticoid therapies. Conclusion: Early detection and appropriate treatment of severe neurological complications can minimize the risk of adverse health outcomes. Evidence based clinical practice guidelines for early detection and treatment would be significant in the management of these devastating neurological complications. Keywords: Hand-foot-and-mouth-disease; Neurological complications; Central Nervous system disease, Aetiology; Clinical features